Investigating Learners’ Competence in the Acquisition of English Spatial Prepositions: The Case of Moroccan EFL 3 rd Year University Students - Younnes Elkhadiri; Youssef Baba Khouya (European Scientific Journal, ESJ, 2019)
Prepositions represent a problematic lexical category for EFL learners. Most of these learners find English prepositions difficult to master. This difficulty stems from the fact that English prepositions are highly polysemous and that they form a unique conceptual category in English. Thus, the usage of prepositions often stands in the way of achieving grammatical fluency and accuracy for the EFL learners. In this respect, the present work attempted to measure Moroccan EFL university students’ competence in the acquisition of English spatial prepositions. It further attempted to check whether the target language specificities and Standard Arabic have some influence on the process of learning. For this purpose, a sample of five English locatives was selected: ‘on’, ‘in’, ‘at’, ‘above’, ‘over’. This set of prepositions represents the most common examples of English locative category. In order to investigate the acquisition of these prepositions by Moroccan EFL learners, three main tests were used for data collection. These tests were completed by 80 Moroccan third-year university students. The first test, Production Task, was used to measure the degree of mastery of the spatial relational prepositions under study. The second test, Acceptability Judgment Task, was devised to examine the receptive knowledge of the students. In this case, the subjects were asked to judge the acceptability of the targeted sentences that contain either correct or wrong prepositions. The third test, Translation Task, in which students were asked to translate a set of Arabic sentences into English; the aim of this test was to check the influence of standard Arabic on the acquisition of English spatial prepositions. The findings of the present study proved that Moroccan students have many difficulties in the use of English locatives since they have made many mistakes in their attempt to place the five targeted prepositions in the right place. Concerning the influence of Standard Arabic, the research revealed that it can facilitate the process of learning when the prepositional systems of both English and Arabic share some similarities. However, it can also be a source of negative transfer, basically when there are noticeable differences between the two languages. In light of the findings of this study, it is recommended that Moroccan teachers should direct the attention of L2 students to the areas of similarities and differences between English and Arabic prepositions. It is argued that the linguistic differences between two prepositional systems are the main factor for committing errors by EFL learners, whereas similarities play a beneficial role in acquiring L2through what is called positive transfer (Lindstromberg, 2010).